Effects of high three pro-nuclei (3PN) proportion incidence on clinical outcomes in the fresh cleavage-stage and blastocyst-stage embryo transfer (ET) cycles. (2nd January 2017) - Li, Mingzhao; Xue, Xia; Zhao, Wanqiu; Li, Wei; Shi, Juanzi
Abstract: Objectives : The aim of this study was to explore the effect of three pro-nuclei (3PN) incidence on clinical outcomes in the fresh cleavage-stage embryo transfer (CSET) and blastocyst-stage embryo transfer (BSET) cycles. Methods : This retrospective cohort study included 1427 CSET cycles, 632 BSET cycles, and 313 elective single BSET cycles from January 2013 to June 2015. The patients were divided into two groups as follows: Group 1 included patients with no 3PN zygotes and Group 2 included patients with >20% 3PN zygotes. Results : We observed that the fertilization rate was significantly lower in 3PN = 0% than 3PN > 20% group ( p < 0.05), but the day-3 grade I + II embryo and day-3 grade I + II + III embryo rates were not significantly different between 3PN = 0% and 3PN > 20% group ( p > 0.05). Interestingly, in the CSET, the implantation (42.87% and 41.76%, p = 0.585) and clinical pregnancy (59.94% and 58.25%, p = 0.538) rates were not significantly different between two groups. In the BSET, the implantation (61.93% and 49.62%, p < 0.001) and clinical pregnancy rates (69.45% and 61.02%, p = 0.043) were significantly higher in 3PN = 0% than 3PN > 20% group. In the elective single BSET, the implantation (68.91% and 61.33%, p = 0.223) and clinical pregnancy rates (68.48% and 61.33%, p = 0.251) were higher in 3PN = 0% than 3PN > 20% group, but there was no significant difference. Conclusions : We concluded that a high 3PN incidence may predict poor outcomes in BSET but not CSET cleavage-stage.